A Clinical Evaluation of Swarna Prashana and Swarna Yoga in the Management of Recurrent Episodes of Kasa (Cough) - Kumar, Sandeep; Chaurasia, Arvind; Bhardhawaj, Ashutosh Kumar; Pandey, Anurag (Journal of Neonatal Surgery, 2025)
Kasa is a condition caused due to Pranavaha Srotodushti, primarily originating from Amashaya. As per Acharya Charaka, “Kāsanāt Kāsaḥ” — the term Kasa denotes the abnormal sound produced during the forceful expulsion of obstructed Vayu. Since childhood is the Kapha-dominant stage of life, children are more prone to disorders of the Pranavaha Srotas, with Kasa being one of the most common. Ayurvedic classics mention several effective formulations for managing this condition. In the present study, the efficacy of Swarna Prashana and Swarna Yoga was evaluated in two separate groups for the management of recurrent episodes of Kasa. Aims and Objectives: To evaluate the efficacy of Swarna Prashana in the management of recurrent Kasa. To evaluate the efficacy of Swarna Yoga in the management of recurrent Kasa. To compare the clinical efficacy of Swarna Prashana and Swarna Yoga in recurrent Kasa. Methods: This was a comparative clinical study with a pre-test and post-test design. A total of 40 patients diagnosed with Kasa, irrespective of gender, were randomly divided into two groups: Group A: Administered Swarna Prashana for 30 days. Group B: Administered Swarna Yoga for 30 days. Results: The therapeutic outcomes were assessed using Wilcoxon’s rank sum test (within the groups) and Mann–Whitney U test (between the groups). The results indicated statistically significant improvement in both groups, with Group A (Swarna Prashana) showing better clinical outcomes than Group B (Swarna Yoga). Conclusion: Both Swarna Prashana and Swarna Yoga are effective in managing recurrent attacks of Kasa in children. However, Swarna Prashana demonstrated comparatively greater efficacy, making it a more promising intervention in recurrent respiratory conditions